Gis-Based Soil Erosion And Sediment Transport Modelling Of Perak River Basin - Yuzaile, Yushafika Roshaini (Universiti Sains Malaysia, 2021)
Riverbank failures are a typical occurrence in Malaysia, particularly during the wet season. The textural composition of riverbanks, which may be represented by the degree or level of soil erodibility, is one of the important variables influencing riverbank erosion. All soil samples collected along the riverbank of the Perak River Basin were sieved and hydrometer tested, and the “ROM” Scale (named after the researchers ROslan and Mazidah) was used to determine the degree of soil erodibility, namely low, moderate, high, very high, and critical along the riverbank, based on the percentage composition of sand, silt, and clay. The potential of riverbank failure at every point along the river may be obtained by determined the soil erodibility level. The use of the Geographical Information System (GIS) is for mapping soil erosion. Interpolation will be made by using GIS to predict the risk of erosion along the Sungai Perak. GIS mapping is used for the best illustration of erosion risk as it presents the risk of a certain location in colours instead of in number. As a result of this vital information, the involved government and private authorities will be able to plan, develop, and implement the most appropriate preventative measures to stop riverbank erosion. Total Suspended Solid (TSS) value will also be compared with the soil composition to seek its relation. TSS result will be obtained from team members to be compared with soil erosion risk level to see whether the location that have high potential risk of soil erosion will effect TSS value. In conclusion, this study is important to protect the environment. However, TSS is not the major study for this research project.